Analysis of power consumption during the machining of epoxy based CFRP - Callisaya, Emanuele Schneider [UNESP]; Alves, Manoel Cléber de Sampaio [UNESP]; Kondo, Marcel Yuzo [UNESP]; Ribeiro, Marcos Valério [UNESP]; Costa, Michelle Leali [UNESP]; Fernandes, Martin Ferreira [UNESP]; Botelho, Edson Cocchieri [UNESP] (Elsevier, 2023)
Carbon fiber-reinforced polymers (CFRP) are extensively applied in the automotive and aeronautic industry due to several advantages that combine resistance properties with the weight reduction of components. The fiber-reinforced thermoset composites are generally manufactured in components close to the final dimensions, and, therefore, need to be machined to meet the final dimensional requirements. The machining must be effective to ensure surface quality and avoid damages and failures. In this work, the milling machining of the epoxy resin matrix Toray E732® reinforced with carbon fibers was studied by the analysis of the power consumption during the process. An experimental investigation was conduced to quantify the effects of input variables (tool rotation, feed per tooth, tool geometry) on the results of maximum power consumption using a Taguchi L8 design. A statistical treatment of variance was applied to determine the influence of the parameters and identification of the best machining condition as well as the most suitable tool geometry to perform the machining. The rotation speed was the most influential parameter with high impact to the power, and the variation from 4000 rpm to 8000 rpm can lead to an increase of 2.5x of the maximum power consumption. The tool geometry also presented a significant influence to the power, the neutral helix geometry favored best surface finish also collaborating to lower the power levels to a maximum of 103 W. Due to the high impact of the rotation and tool geometry, the influence of the feed was minimized. Therefore, to machine the carbon reinforced epoxy composite, it is recommended to apply the lowest levels of the selected parameters, since the cutting mechanisms favor the reduction of power consumption to a maximum of 77 W along with the reduction of cutting forces during machining.
Keywords: CFRP; Machining; Milling; Power consumption